Methods of cartographic representation of population distribution and density in Al-Sweida Governorate (Damascus University Journal of arts and humanities sciences, 2023)
The map is a visual base for geographical information, and in order to understand and read this rule, the appearances on it must be represented by appropriate symbols, showing their characteristics and relationships among them, according to the rules of visual perception. It is easy to understand, The research aims to design maps of the distribution of the population in the Al-Sweida Governorate using the best cartographic representation methods, as the population of Al-Sweida Governorate reached 409,170 people until 2018, according to the data of the statistical group. Relative columns, gradient, relative shading and isolines, Depending on the descriptive, analytical and cartographic method. The most important findings of the research are that the best symbols to represent the geographical distribution of the population were the points organized in size, and the relative columns are among the best quantitative position symbols to express the numerical distribution of the population, and the adoption of gradient colors is the best to represent the population density, whether it is general or net.
Keywords: cartographic representation; visual perception